Chronic myelomonocytic leukemia with ring sideroblasts/SF3B1 mutation presents with low monocyte count and resembles myelodysplastic syndromes with-RS/SF3B1 mutation in terms of phenotype and prognosis - Xicoy, Blanca; Pomares, Helena; Morgades, Mireia; Germing, Ulrich; Arnan, Montserrat; Tormo, Mar; Palomo, Laura; Orna, Elisa; Della Porta, Matteo; Schulz, Felicitas; Díaz-Beya, Marina; Esteban, Ada; et al. (Frontiers in Oncology, 2024)
Chronic myelomonocytic leukemia (CMML) and myelodysplastic syndromes (MDS) with ring sideroblasts (RS) or SF3B1 mutation (MDS-RS/SF3B1) differ in many clinical features, but share others, such as anemia. RS and SF3B1 mutation can also be found in CMML. We compared CMML with and without RS/SF3B1 and MDS-RS/SF3B1 considering the criteria established by the 2022 World Health Organization classification. A total of 815 patients were included (CMML, n=319, CMML-RS/SF3B1, n=172 and MDS-RS/SF3B1, n=324). The percentage of RS was ≥15% in almost all CMML-RS/SF3B1 patients (169, 98.3%) and most (125, 72.7%) showed peripheral blood monocyte counts between 0.5 and 0.9 x10 9 /L and low risk prognostic categories. CMML-RS/SF3B1 differed significantly from classical CMML in the main clinical characteristics, whereas it resembled MDS-RS/SF3B1. At a molecular level, CMML and CMML-RS/SF3B1 had a significantly higher frequency of mutations in TET2 (mostly multi-hit) and ASXL1 (p=0.013) and CMML had a significantly lower frequency of DNMT3A and SF3B1 mutations compared to CMML/MDS-RS/SF3B1. Differences in the median overall survival among the three groups were statistically significant: 6.75 years (95% confidence interval [CI] 5.41-8.09) for CMML-RS/SF3B1 vs. 3.17 years (95% CI 2.56-3.79) for CMML vs. 16.47 years (NA) for MDS-RS/SF3B1, p<0.001. Regarding patients with CMML and MDS, both with SF3B1 mutation, survival did not significantly differ. CMML had a higher risk of transformation to acute myeloid leukemia (24% at 8 years, 95%CI 19%-30%). In conclusion, CMML-RS/SF3B1 mutation resembles MDS-RS/SF3B1 in terms of phenotype and clearly differs from CMML. The presence of ≥15% RS and/or SF3B1 in CMML is associated with a low monocyte count. SF3B1 mutation clearly improves the prognosis of CMML.